Securitization of religion in Central Asia: balance between national security and religious freedom (Journal of Philosophy Culture and Political Science, 2024)
This article examines the process of securitization of religion in the countries of Central Asia, focusing on finding the optimal balance between ensuring national security and preserving the constitutional right to freedom of religion. The analysis is based on the study of the legislative framework, statistical data and expert assessments, which allows for a comprehensive consideration of the transformation of state policy in the religious sphere. The study focuses on the mechanisms of control over religious activity and their impact on society. Particular attention is paid to the potential risks of radicalization of believers that may arise because of excessive government regulation. The methodology of the work includes comparative analysis, content analysis of regulatory documents and media materials, as well as statistical analysis of demographic data. The results of the study demonstrate the duality of the consequences of the securitization of religion in the region. On the one hand, this process helps to reduce the risks of religious extremism, which is a positive factor а ensuring national security. On the other hand, strict control measures can provoke an increase in social tension and radicalization of certain groups of believers, which creates new challenges for public policy. Based on the findings, the article offers recommendations for improving state policy in the religious sphere. These recommendations consider the need to maintain a delicate balance between ensuring security and protecting freedom of conscience. The proposed measures are aimed at creating a more flexible and inclusive system of regulating religious activity that could effectively counter extremism without infringing on the rights of law-abiding believers. In conclusion, the importance of further research in this area is emphasized for developing effective strategies for managing the religious sphere in the changing geopolitical and social reality of Central Asia.Keywords: securitization of religion, Central Asia, national security, freedom of religion, religious policy, radicalization, state regulation